Design of a "test Cell" to be located at 4500 masl in a high Andean region of Peru and dynamic simulation of the thermal performance of housing wall materials - Molina J.O. (2020)
The objective of the present study is to select appropriate wall materials for houses in high Andean regions based on the measurements of the thermal behavior of construction materials using a "Test Cell" under real environmental conditions. It will be the first "Test Cell" to be installed in Peru, in Imata-Arequipa, at 4500 masl. The design and thermal analysis of the "Test Cell" are presented using dynamic simulations with the EnergyPlus program. Initially, the thermal performance of adobe, a traditional construction material in rural regions of Peru, is simulated using real meteorological data recorded in Imata between August 18 and 24, 2018, a period with low temperatures (-12.6 °C). © Published under licence by IOP Publishing Ltd.